Kekerasan Simbolik Pada Janda di Desa Dwitiro Kecamatan Bontotiro Kabupaten Bulukumba - Sarina Sarina; Supriadi Torro; Muhamad Ihsan Azhim (Phinisi Integration Review, 2022)
This study aims to discover: 1) the description of symbolic violence on widows at Dwitiro Village and 2) the impact of symbolic violence on widows at Dwitiro Village. This type of study employed descriptive qualitative research by determining the number of informants consisting of 8 informants selected by purposive sampling technique with the criteria that widows have had widow status for more than 2 years and aged 27-47 years. Data collection techniques employed observation, interviews, and documentation. The data analysis technique employed data reduction, data presentation, and conclusion drawing. The data validation technique used was source triangulation. The results of the study reveal that 1) there are two descriptions of symbolic violence on widows at Dwitiro Village, namely in the form of euphemism and censorism. The symbolic violence in the form of euphemisms are necessity and prohibition. The symbolic violence in the form of censorism is inappropriate, 2) the impact of symbolic violence on widows at Dwitiro Village is divided into two aspects, namely the impact on the psychological aspect and the social aspect. The impact in the psychological aspect includes fatalism and apathy, while the impact in the social aspect is withdrawing from the social environment as well as a conflict between the widow and her family